Management of acute lower extremity deep venous thrombosis in a patient with duplicated inferior vena cava and contraindication to anticoagulation: case and review of the literature. (4th June 2018) - Patel, Shrinil; Cheema, Anmol; Karawadia, Tejas; Carson, Michael
Abstract : Duplication of the inferior vena cava (DIVC) is an uncommon embryological anatomic phenomenon. We report a 63-year-old woman with extensive right leg deep vein thrombosis who required an IVC filter due to contraindications for anticoagulation, but was found to have DIVC which required the placement of two IVC filters with good result. This report will review and summarise past reports of DIVC management to provide a guide for future clinicians, and review the embryological development, diagnosis and IVC filter placement options as they are based on the type of anatomic malformation encountered.